2018
DOI: 10.1097/md.0000000000010802
|View full text |Cite
|
Sign up to set email alerts
|

Rare case of squamous cell carcinoma arising in a recurrent ovarian mature cystic teratoma of a young woman

Abstract: Rationale:Malignant transformations of ovarian mature cystic teratomas (MCTs) occur rarely, especially in young women. Although it is extremely difficult to diagnose them, serum tumor marker level testing in combination with the use of imaging techniques may be useful in preoperative diagnosis.Patient concerns:We present the case of a 31-year-old Chinese woman with the malignant transformation of an ovarian MCT. The patient had a history of oophorocystectomy due to an MCT of the right ovary 6 years prior and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…It is mostly observed in postmenopausal women with an average age of 58.2 years as compared to 37.5 years in MCT . Some cases of malignant transformation of MCT have been reported in younger patients . Preoperative detection of malignant transformation of MCTs is challenging due to nonspecific tumor markers and imaging findings …”
Section: Discussionmentioning
confidence: 99%
“…It is mostly observed in postmenopausal women with an average age of 58.2 years as compared to 37.5 years in MCT . Some cases of malignant transformation of MCT have been reported in younger patients . Preoperative detection of malignant transformation of MCTs is challenging due to nonspecific tumor markers and imaging findings …”
Section: Discussionmentioning
confidence: 99%
“…Due to the different components of a teratoma, there can be various malignant transformations, such as squamous cell carcinomas (75%-80%), adenocarcinomas (7%), sarcomas (7%), basal cell carcinomas, sebaceous gland carcinomas, malignant melanomas, small cell lung cancers, transitional cell carcinomas, clear cell carcinomas, and gliomas [1,[3][4][5][6] . The patholog-ical diagnosis confirmed that this case was a teratoma accompanied by the malignant transformation of a sebaceous gland carcinoma, which is very rare.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most common symptoms are a palpable abdominal mass, abdominal distension, and hypogastralgia, while the mild symptoms include lumbago, dysuria, weight loss, rupture, or torsion of the cyst. With a malignant transformation invading the surrounding organs or lymph nodes, clinical symptoms, such as a stomachache, leg pain, and lower extremity and vulvar edema, are aggravated [1,3,8] . In this case, the tumor in the left ovary was detected by B-mode ultrasound, and there were no clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations